MICRONUTRIENT DEFICIENCY IN THE” MOTHER-CHILD " SYSTEM DETECTION ALGORITHM (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
According to WHO, anemia of pregnancy is a common condition affecting 30–80% of women worldwide, complicating pregnancy, negatively affecting birth outcomes, and the health of the fetus and child. remains (WHO, 2015). The health of the future generation is determined by many factors and, to a greater extent, directly or indirectly, by the health of the mother, so issues of maternal and child health can be comprehensively considered and are considered as a single problem. According to the World Bank, the overall nutritional status of children under 5, women of reproductive age (15–49 years), and pregnant women in Uzbekistan has been steadily improving over the past two decades. A national study conducted in 2008 showed that just over 34 percent of women of reproductive age suffered from anemia. The study also found that iron and folate deficiency were observed in 48 and 29 percent of adult women, respectively.